The Effect of Work Stress and Readiness to Use E-BMD on the Performance of Asset Management Staff at the Regional Secretariat of Jombang Regency, With Organizational Commitment as an Intervening Variable - Arista Nurul Cahyati; Choirul Nikmah (Universitas KH. Abdul Chalim Mojokerto, 2026)
The progress of modernization has influenced various aspects of human life, including the workplace. Through this progress, technological advancements and digitalization have taken shape and made daily activities more convenient. However, in government agencies in Indonesia, the implementation of digitalization remains suboptimal, even though it should be utilized to support the implementation of good governance. The E-BMD application serves as a digital innovation in asset management. This study aims to analyze the influence of work-related stress and readiness to use E-BMD on the performance of asset management staff at the Jombang Regional Secretariat, with organizational commitment as an intervening variable. This study employs a quantitative approach with an explanatory research design. Data were collected through the distribution of questionnaires to 50 asset management staff involved in the use of E-BMD. Data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) through outer and inner model testing to assess validity, reliability, and relationships among variables. The results indicate that readiness to use E-BMD has a positive and significant effect on employee performance and organizational commitment. Organizational commitment also has a positive and significant effect on employee performance. Conversely, job stress has a negative and significant effect on both organizational commitment and employee performance. Furthermore, organizational commitment was found to partially mediate the effects of job stress and readiness to use E-BMD on employee performance. These findings indicate that the success of E- BMD system implementation is not solely determined by technological readiness but is also influenced by employees’ levels of work-related stress and organizational commitment. Therefore, improved performance among asset management staff can be achieved by enhancing technological readiness, effectively managing work-related stress, and increasing organizational commitment.